How Corporate Social Responsibility Affects Employees’ Organizational Commitment: A Study of the Egyptian Market - Emam, Yumna (AUC Knowledge Fountain, 2014)
A growing number of studies has investigated the multiple dimensions of Corporate Social Responsibility (CSR); however, very few have studied its effect on organizational commitment, especially in a country as Egypt. This research examines the relationship between employees’ perceptions of Corporate Social Responsibility (CSR) and organizational commitment within a model that draws on Social Identity Theory (SIT). The analysis is based on a sample of 326 employees from different companies in Egypt. The results emphasize that there is a positive correlation between employee’s perceptions of CSR importance and organizational commitment via a mediating factor, which is satisfaction with CSR activities and programs. It builds upon the SIT which explains the desire of employees to be identified with an entity they are proud of and perceive as a good corporate citizen. This research should act as a guideline for corporations to determine the significance of adding CSR in their mission and vision statements and work to live by these standards in order to maintain the organizational commitment of their respective employees.